Penguatan pendidikan karakter berbasis high order thinking skill melalui seni tari di pendidikan dasar Kabupaten Blitar - Saraswati, Ayu Ridho; Sari, Dyan Indah Purnama; Jannan, Mohamad Miftakul; Kamilina, Ismi Imani (Trihayu: Jurnal Pendidikan Ke-SD-an, 2025)
Art is synonymous with freedom. Contrary to this statement, one of the functions of art is a medium for instilling character values based on a person's critical thinking through learning. The above explanation is the attraction of this study to analyze that dance can instill the value of strengthening character education based on high order thinking skills in the realm of basic education in Blitar Regency. The location of the research is in Doko District, precisely in the basic education unit with Islamic religious characteristics, namely Madrasah Ibtidaiyah Darul Ulum, the second in general basic education, namely the 01 Genengan State Elementary School. This study uses a qualitative approach with data triangulation with interview, observation, and documentation techniques. The results of the study show that as long as students participate in this activity, with the 'freedom' of dance activities, students show the value of Strengthening Character Education with the criticality that arises from students' behavior during the dance process. The strengthening of character education consisting of nationalism, religious, mutual cooperation, integrity, and independence can be seen in the high order thinking skills activities that exist in the dance process, namely remembering, analyzing, evaluating and creating.